Corrosion resistance of magnesium phosphate cement under long-term immersion in different solutions. (1st May 2023) - Li, Chaozhong; Meng, Xiaokai; Zhu, Jincai
Abstract: Magnesium phosphate cement (MPC) is widely utilised in engineering. However, it may be subject to corrosion in the Western Chinese saline soil environment. This study analysed the factors of magnesium phosphorus ratio, borax content, water binder ratio and fly ash content. Mix proportions of MPC were devised through orthogonal testing. The corrosion performance of MPC specimens in water, 5% Na2 SO4 solution, 5% NaCl solution and saline soil solution were analysed in terms of mass loss and the strength anti-corrosion coefficient. The corrosion mechanisms of MPC in different solutions were analysed by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Thermogravimetric and differential scanning calorimetry (TG-DSC) and Scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS). There were no obvious changes in MPC appearance or morphology after soaking in different solutions for 180 days. The mass loss was < 5% and the strength loss was < 25%, indicating that MPC has good resistance to saline soil and other saline solutions. The strength anti-corrosion coefficients of MPC soaked in various solutions for 180 days were > 0.75, and the influences on strength can be ranked as follows: 5% Na2 SO4 solution > saline soil solution > water > 5% NaCl solution. On the basis of TG-DSC, FTIR and XRD analyses, when MPC was soaked in different solutions for 180 d, the contents of the hydration product MgKPO4 ·6H2 O (MKP) were ranked as water > 5% NaCl solution > saline soil solution > 5% Na2 SO4 solution. SEM-EDS analysis shows that MKP was corroded to varying degrees after the MPC was soaked in different solutions, with the 5% Na2 SO4 solution causing the greatest corrosion. Graphical abstract: Image 1 Highlights: Strength loss in MPC immersed in various solutions for 180 d was investigated. The long-term corrosion resistance of MPC to saline soil solution was studied. The behaviour and mechanism of MPC corrosion in saline soil solution were analysed.